Analysis of the Budget for the Palm Oil Replanting Project at PT. Andalas Agri in Seluma Regency - M. Zaidul Kirom; Sela Septi Andri; Catur Panggih Prayogo (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This research was conducted at PT. Agri Andalas, Seluma Regency, Bengkulu Province. The purpose of this research is to find out and analyze the budget of PT. Agri Andalas in Seluma Regency and see if it complies with applicable regulations or not. The analytical method used in this study is a qualitative method, where the data collected is based on the results of interviews with respondents related to research. The results of the study indicate that the budget prepared has not been very efficient and has not been proposed by PT. Agri Andalas because the projects that are being carried out have not been running properly.